2019
DOI: 10.18805/ag.d-171
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Effects of a Single Dose of PLGA Nanoparticles Encapsulated Peptide in Broilers in Comparison to Traditional Vaccines against Infectious Bursal Disease

Abstract: Infectious bursal disease is a viral poultry disease that causes economic losses. This study aimed to evaluate the white blood cells count (WBCs count), differential count, antibody (Ab) titration against IBDV and interferone gamma (INF-ã) responses in broiler administered traditional and prepared nanovaccines. A total of 98 broiler chicks (Ross 308) were used to evaluate the immunological responses. They were devided into G1(Control); G2- (Traditional vaccine); G3(PLGA nanoparticle); G4(160 µg of peptide load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, there is an urgent need to develop new, more-potent vaccines to control IBDV infection. Interestingly, a research group recorded a significant increase in both humoral and cellular immune responses in broiler chickens vaccinated with a PLGA nanoparticle vaccine when compared to chickens vaccinated with the traditional IBDV vaccine [3]. Another study showed that graphene oxide (GO) sheets and silver nanoparticle-anchored graphene oxide (GO-Ag) sheets have antiviral effects against non-enveloped IBDV and enveloped feline coronavirus (FCoV) [16].…”
Section: Infectious Bursal Disease Virus (Ibdv)mentioning
confidence: 99%
“…Therefore, there is an urgent need to develop new, more-potent vaccines to control IBDV infection. Interestingly, a research group recorded a significant increase in both humoral and cellular immune responses in broiler chickens vaccinated with a PLGA nanoparticle vaccine when compared to chickens vaccinated with the traditional IBDV vaccine [3]. Another study showed that graphene oxide (GO) sheets and silver nanoparticle-anchored graphene oxide (GO-Ag) sheets have antiviral effects against non-enveloped IBDV and enveloped feline coronavirus (FCoV) [16].…”
Section: Infectious Bursal Disease Virus (Ibdv)mentioning
confidence: 99%